PEMBERDAYAAN PEKEBUN KELAPA SAWIT SWADAYA MENUJU PEMBANGUNAN PERKEBUNAN BERKELANJUTAN DI KABUPATEN BERAU: PEMBERDAYAAN PEKEBUN KELAPA SAWIT SWADAYA MENUJU PEMBANGUNAN PERKEBUNAN BERKELANJUTAN DI KABUPATEN BERAU - Darmono (ECO-BUILD, 2021)
Empowerment of independent oil palm smallholders aims to realize the sovereignty and independence of independent oil palm smallholders in order to improve the level of welfare, quality, and a better life; protect Smallholders from crop failure and price risk; provide infrastructure and facilities needed to develop plantation business; develop plantation financing institutions that serve the interests of plantation businesses; improve the capability and capacity of independent smallholders and independent plantation institutions in carrying out plantation business that is productive, advanced, modern, added value, competitive, has market share and is sustainable; as well as providing legal certainty for the implementation of independent oil palm plantation businesses.